Singapore’s Threat Outlook 2017: The Terrorist Challenge Ahead - Mahzam, Remy (2017)
The 2016 Global Terrorism Index (GTI) report by the Institute for Economics and Peace has ranked Singapore as one of the safest countries in the world, maintaining its position of last year. While this attests to the efficacy of Singapore’s counter-terrorism efforts, the unceasing threat of terrorism calls for steadfast vigilance, preparedness and resilience at all levels of society.